2020
DOI: 10.1002/jat.4075
|View full text |Cite
|
Sign up to set email alerts
|

Novel toxicity of tris(1,3‐dichloro‐2‐propyl) phosphate in adult male rats

Abstract: The widespread use of tris(1,3‐dichloro‐2‐propyl) phosphate (TDCIPP) as a flame retardant has led to its release to the environment. Thus, the toxicological effects of TDCIPP on humans and animals are of importance. For better understanding of its potential toxicities, TDCIPP (250, 500, or 650 mg/kg/day) or vehicle control was administrated orally to adult male Wistar‐Imamichi rats for 7 days. After the final administration of compounds, organ weights, histopathology, blood biochemistry, and hematology were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Serum iron and UIBC are indices that are mainly used in the diagnosis of anemia. From the toxicity results of TDCIPP in 9‐week‐old rats (Kobayashi et al, 2021) and the results of this study, RBC counts and Hb, and Ht levels were decreased along with a decrease in reticulocyte counts. TDCIPP might induce renal anemia by decreasing the production of erythropoietin by the kidneys.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Serum iron and UIBC are indices that are mainly used in the diagnosis of anemia. From the toxicity results of TDCIPP in 9‐week‐old rats (Kobayashi et al, 2021) and the results of this study, RBC counts and Hb, and Ht levels were decreased along with a decrease in reticulocyte counts. TDCIPP might induce renal anemia by decreasing the production of erythropoietin by the kidneys.…”
Section: Discussionsupporting
confidence: 62%
“…This study clarified that the toxic effects of exposure to high concentrations of TDCIPP in adulthood are affected by neonatal exposure. We previously reported the effects of high‐dose exposure to TDCIPP over 1 week in 9‐week‐old Wistar–Imamichi male rats and observed hepatotoxicity, nephrotoxicity, spleen atrophy, anemia with decreased reticulocyte counts, and decreased ALP levels (Kobayashi et al, 2021). Similarly, as reported in previous studies, the present investigation identified changes of liver function (increases in liver weight and ALB and ALT levels), changes of kidney function (increases of kidney weight and BUN and CRE levels), and anemia symptoms associated with decreased spleen weight and decreased reticular erythrocyte counts as the main effects of the TDCIPP exposure in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the effect of 7 days of TDCIPP oral administration on the epididymal sperm parameters was investigated. The present study found that a dose of 250 mg/kg/day, which does not cause overt toxicities [13], affected some of the sperm parameters. Unexpectedly, although antiandrogenic substances typically decrease sperm parameters such as sperm number, motility, and velocity in adulthood [15,18,20,22], TDCIPP induced an increase in some of these parameters.…”
supporting
confidence: 46%
“…13674-87-8, Purity: >93.0%) dissolved in sesame oil (250 mg/kg/day group: n = 6, 650 mg/kg/day group: n = 6) for 7 days. The dose of 650 mg/kg/day caused overt hepatic and renal toxicity, but the dose of 250 mg/kg/day did not [13].…”
mentioning
confidence: 90%
See 1 more Smart Citation